Автоматизація проектних робіт, моніторингу та контролю у будівництві (на прикладі розвинутих країн) - Шатров, С. В. (Ways to Improve Construction Efficiency, 2013)
The questions of article contains the composition and preparation of project documentation: the wording of the functional purpose of construction, site selection, determination of capacity of facilities and processes. Basic requirements for the introduction of computer-aided design in manufacturing.